Intraoperative Localization of Vascular Malformation of Small Bowel by Selective Intra-arterial Dye Injection - Eshpuniyani, Priya B. (Medknow Publications, 2010)
Angiomatous malformation is the most common vascular abnormality, accounting for 30-40% cases of obscure GI bleeding from small bowel. Surgical resection is the treatment of choice in severe or recurrent hemorrhage requiring multiple blood transfusions. However, the diffuse nature of the lesions poses a challenge to localize them accurately preoperatively, for exact resection. We present a case in which we have used selective mesenteric angiography with selective cannulation and exact localization of the lesion by injecting dye such as methylene blue, indigo carmine, and fluorescein, to localize the angiomatous malformation before surgical resection and also to determine the exact resection to be done.